Improving Cofactor Promiscuity of HMG-CoA Reductase from Ruegeria pomeroyi Through Rational Design - Haizhao Xue; Yanzhe Huang; Aabid Manzoor Shah; Xueying Wang; Yinghan Hu; Lingyun Zhang; Zongbao K. Zhao (Biomolecules)
The mevalonate pathway is crucial for synthesizing isopentenyl pyrophosphate (IPP), the universal precursor of terpenoids, with 3-hydroxy-3-methylglutaryl-CoA reductase (HMGR) serving as the rate-determining enzyme that catalyzes the reduction of 3-hydroxy-3-methylglutaryl-CoA (HMG-CoA) to mevalonate, requiring NAD(P)H as an electron donor. Improving the cofactor promiscuity of HMGR can facilitate substrate utilization and terpenoid production by overcoming cofactor specificity limitations. In this study, we heterologously expressed rpHMGR from Ruegeria pomeroyi in Escherichia coli BL21(DE3) for the first time and established that it predominantly utilizes NADH. To broaden its cofactor usage, we employed Molecular Operating Environment (MOE)-assisted design to engineer the cofactor binding site, creating a dual-cofactor-utilizing mutant, D154K (the substitution of aspartic acid with lysine at residue 154). This mutant exhibited a significant 53.7-fold increase in activity toward NADPH, without compromising protein stability at physiological temperatures. The D154K mutant displayed an optimal pH of 6, maintaining over 80% of its catalytic activity across the pH range of 6–8, regardless of whether NADH or NADPH was the cofactor. These findings highlight the value of rational design, enhance our understanding of HMGR-cofactor recognition mechanisms, and provide a foundation for future efforts to optimize and engineer HMGR for broader cofactor flexibility.